Effect of trimetazidine treatment on the transient outward potassium current of the left ventricular myocytes of rats with streptozotocin-induced type 1 diabetes mellitus - Xiang,Yu-luan (2012)
Cardiovascular complications are a leading cause of mortality in patients with diabetes mellitus (DM). The present study was designed to investigate the effects of trimetazidine (TMZ), an anti-angina drug, on transient outward potassium current (Ito) remodeling in ventricular myocytes and the plasma contents of free fatty acid (FFA) and glucose in DM. Sprague-Dawley rats, 8 weeks old and weighing 200-250 g, were randomly divided into three groups of 20 animals each. The control group was injected with vehicle (1 mM citrate buffer), the DM group was injected with 65 mg/kg streptozotocin (STZ) for induction of type 1 DM, and the DM + TMZ group was injected with the same dose of STZ followed by a 4-week treatment with TMZ (60 mg·kg-1·day-1). All animals were then euthanized and their hearts excised and subjected to electrophysiological measurements or gene expression analyses. TMZ exposure significantly reversed the increased plasma FFA level in diabetic rats, but failed to change the plasma glucose level. The amplitude of Ito was significantly decreased in left ventricular myocytes from diabetic rats relative to control animals (6.25 ± 1.45 vs 20.72 ± 2.93 pA/pF at +40 mV). The DM-associated Ito reduction was attenuated by TMZ. Moreover, TMZ treatment reversed the increased expression of the channel-forming alpha subunit Kv1.4 and the decreased expression of Kv4.2 and Kv4.3 in diabetic rat hearts. These data demonstrate that TMZ can normalize, or partially normalize, the increased plasma FFA content, the reduced Ito of ventricular myocytes, and the altered expression Kv1.4, Kv4.2, and Kv4.3 in type 1 DM.